A human antibody against Zika virus crosslinks the E protein to prevent infection - S. Saif Hasan (Nature Portfolio, 2017)
The human monoclonal antibody ZIKV-117 has demonstrated therapeutic potential against Zika while showing no cross-reactivity to other flaviviruses. Here the authors present a cryo-EM structure of the ZIKV strain H/PF/2013 in complex with the ZIKV-117 Fab, shedding light on its neutralization mechanism.